1947
DOI: 10.2307/1969172
|View full text |Cite
|
Sign up to set email alerts
|

Products of Cocycles and Extensions of Mappings

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
216
0
3

Year Published

1966
1966
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(222 citation statements)
references
References 8 publications
1
216
0
3
Order By: Relevance
“…Obtaining those strange sign factors is another breakthrough that allows us to obtain topological fermionic path integral beyond (1+1) dimensions. It appears that those sign factors are related to a deep mathematical structure called Steenrod squares [72,73] Different vertex orders give rise to different branching structures. It turns out that all the valid branching structures give rise to the same condition (47).…”
Section: (3+1)d Casementioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining those strange sign factors is another breakthrough that allows us to obtain topological fermionic path integral beyond (1+1) dimensions. It appears that those sign factors are related to a deep mathematical structure called Steenrod squares [72,73] Different vertex orders give rise to different branching structures. It turns out that all the valid branching structures give rise to the same condition (47).…”
Section: (3+1)d Casementioning
confidence: 99%
“…− n 3 (g 0 ,g 1 ,g 2 ,g 3 )m 2 (g 0 ,g 3 ,g 4 ) − n 3 (g 1 ,g 2 ,g 3 ,g 4 )m 2 (g 0 ,g 1 ,g 4 ) − n 3 (g 0 ,g 1 ,g 2 ,g 3 )m 2 (g 0 ,g 3 ,g 5 ) − n 3 (g 1 ,g 2 ,g 3 ,g 5 )m 2 (g 0 ,g 1 ,g 5 ) − n 3 (g 0 ,g 1 ,g 2 ,g 4 )m 2 (g 0 ,g 4 ,g 5 ) − n 3 (g 1 ,g 2 ,g 4 ,g 5 )m 2 (g 0 ,g 1 ,g [72,73]. This realization will allow us to generalize Eq.…”
Section: Appendix F: Calculate Group Supercohomology Classmentioning
confidence: 99%
“…As was suggested by one of the referees, for the case d = 2k − 1, the existence of an equivariant map is characterized by (an equivariant version of) a theorem of Steenrod [Ste47], which involves the first cohomological obstruction plus another apparently computable invariant (a Steenrod square operation in cohomology). This might also yield even a polynomial-time decision algorithm, but some computational issues still need to be checked.…”
Section: Appendix B the Deleted Product Obstructionmentioning
confidence: 99%
“…In 1947, Steenrod [21] introduced the Steenrod squares Sq k in terms of cocycles in simplicial cochain complex by modifying the Alexander-Ĉech-Whitney formula for the cup product construction. Serre [16] showed that they generate all stable operations in cohomology over F 2 under composition.…”
Section: Preliminariesmentioning
confidence: 99%